The Effect of Experience and Time Budget Pressure on the Auditor’s Ability to Detect Fraud with Understanding of Red Flags as a Moderating Variable - Pande Putu Diah Maharani; I Ketut Suryanawa; Ni Ketut Rasmini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Financial statements play an important role in providing relevant, reliable, and trustworthy financial information to stakeholders. Although auditors are responsible for ensuring the fairness of these statements, cases of undetected financial fraud still occur. This research seeks to empirically examine the effect of experience and time budget pressure on the auditor’s ability to detect fraud, with an understanding of red flags as a moderating variable. The research was conducted on auditors who work in Public Accounting Firms (PAFs) in Bali. The sample was determined using purposive sampling technique and 94 auditors were obtained as a sample. Data was collected through a survey method using a structured questionnaire distributed to respondents. The analytical methods used include multiple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that experience has a positive effect, and time budget pressure has a negative effect on the auditor’s’ ability to detect fraud. Furthermore, red flags strengthen the effect of experience and time budget pressure on the auditor’s ability to detect fraud. The findings provide valuable insights for auditors to manage their work focus effectively and for public accounting firms to allocate audit time proportionally, ensuring optimal awareness of red flags even under high time pressure.